Influence of Planetary Ball Mill Parameters on Powder Flowability of AlSi10Mg with Niobium Carbide Using Central Composite Design (CCD) - Raj Mohan R; Venkatraman R; Raghuraman S; Manoj Kumar P; Rajneesh Sharma; null Ankit; Atul Sarojwal; Rajkumar S (Advances in Materials Science and Engineering)
The hypoeutectic aluminum alloy (AlSi10Mg) is a well-known candidate material used predominantly for its processability and inherent characteristics in metal-based additive manufacturing. Besides, transition metal carbide, such as niobium carbide (NbC), is added to the AlSi10Mg, enhancing its mechanical properties and preferably its wear resistance to the matrix. However, in additive manufacturing, the mixed powder’s flowability is a prerequisite for determining the final properties of the specimens. In this study, mixed powder flowability analysis was carried out through the regular mixing of AlSi10Mg with a varying weight percentage of NbC conducted in the planetary ball mill with different time, speed, and NbC composition following the Central Composite Design (CCD), with a total of 20 experiments. Here, regular mixing was preferred to retain the morphology of the AlSi10Mg (spherical shape) instead of ball milling, which contributes to the degradation of the powder’s shape and size. Finally, based on the combined analysis of apparent density (AD), tapped density (TD), and static angle of repose (SAoR), the flowability characteristics of the mixed powders (AlSi10Mg  +  X % NbC) were evaluated. The optimum combination (AlSi10Mg + X% NbC) was attained based on the composite desirability criteria.